ANALISIS PEMAHAMAN MAKNA SHALAT DALAM PERSPEKTIF PENDIDIKAN ISLAM PADA SISWA KELAS VIII A SMP NEGERI 24 BUTON TENGAH - Wilda Asriani; La Jusu; Abdul Rahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of understanding of the meaning of prayer (shalat) among eighth-grade students of Class VIII A at SMP Negeri 24 Buton Tengah from the perspective of Islamic education, as well as to identify the factors that influence it. The study employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews with 12 students and one Islamic Education teacher, and documentation. Data analysis followed the interactive model developed by Miles, Huberman, and Saldaña, with data credibility ensured through source triangulation and method triangulation. The findings reveal that students’ understanding of the meaning of prayer remains at a basic cognitive level: the majority of students define prayer merely as a religious obligation and a means of obtaining divine reward, while eight out of twelve students admitted that they do not understand the meaning of the Arabic recitations they perform during prayer. At the affective dimension, some students reported experiencing a sense of inner calm after praying; however, this experience has not yet been consciously connected to the deeper spiritual meaning of the worship. The reflective-applicative dimension proved to be the weakest, as most students were unable to meaningfully relate the values of prayer to their concrete daily behavior. Students’ understanding was influenced by four primary factors: the role of parents, guidance from the Islamic Education teacher, peer environment, and students’ individual motivation and self-awareness. These findings affirm that consistent ritual habituation must be complemented by reflective, meaning-centered learning, as part of the broader effort to realize quality religious education in alignment with SDG 4 on Quality Education.